AB0256 PREDICTION OF DISEASE RELAPSES BY MULTIBIOMARKER DISEASE ACTIVITY SCORE AND AUTOANTIBODY STATUS IN RA PATIENTS TAPERING DMARD TREATMENT – AN UPDATE OF THE RETRO STUDY. (June 2019) - Hagen, Melanie; Tascilar, Koray; Reiser, Michaela; Valor, Larissa; Haschka, Judith; Kleyer, Arnd; Hueber, Axel; Manger, Bernhard; Schett, Georg; Rech, Jürgen; ,
Abstract : Background: Achieving remission is the ultimate treatment goal in patients with rheumatoid arthritis (RA). With the development and wider use of highly effective disease modifying anti-rheumatic drugs (DMARD) about half of RA patients reach the disease remission state (1), raising the question about tapering or stopping anti-rheumatic treatment and appropriate predictors (2). Objectives: The purpose was to analyze the effect of multi-biomarker disease activity (MBDA) score and anti-citrullinated protein (ACPA) on relapse rates in RA patients in sustained remission enrolled in the prospective randomized controlled RETRO study (3, 4, 5). Methods: MBDA scores and ACPA status were determined in the baseline samples of patients in sustained DAS28-ESR remission fulfilling RETRO inclusion criteria. Patients were unblended and either continued DMARDs (Control), tapered dose by 50% (Taper) or stopped DMARDs after tapering (Taper/Stop) for one year according to the RETRO study protocol. MBDA and ACPA status were used as relapse predictors. Relapse was defined as the loss of a DAS28-ESR remission. We calculated incidence of flares and 95% Poisson confidence intervals by baseline ACPA and MBDA status in each study group (double negative, single positive, double positive). We compared the risk of flare in the treatment arms with a Cox regression model and calculated hazard ratios (HR) and 95% confidence interval (CI) for relapses. Results: Serum samples and follow-up data of 203 patients included in the RETRO trial were analyzed. A flare was observed in 8/59 patients (13.6%) in the Control group, 24/60 (40.0%) patients in the Taper group and 37/68 (54.4%) patients in the Taper/Stop group among the 187 patients that completed their 1-year follow-up. HR (95%CI) for a relapse was 3.43 (1.54-7.66) in the taper group and 5.32 (2.47-11.46) for the control group. HR of flare of a positive MBDA and ACPA was 4.00 (1.72-9.31) compared to a negative MBDA and ACPA. Flare incidence did not differ with baseline MBDA/ACPA status in the control group, whereas in the taper/stop group, number of positive biomarkers could identify three distinct subgroups with a graded incidence of flare (Figure). Conclusion: Tapering or stopping DMARDs after stable remission was associated with an increased risk of RA flares. Incidence of flares in ACPA/MBDA double-negative patients after tapering and stopping RA treatment was comparable to those that continued treatment within the precision limits of our subgroups. Lack of blinding is a shortcoming of our study. References: [1] Aga AB et al. Ann Rheum Dis. 2013;74:381-8. [2] Schett G et al. Ann Rheum Dis. 2016 Aug;75(8):1428-373. [3] Haschka J et al, Ann Rheum Dis. 2016;75:45-51. [4] Rech J et al, Ann Rheum Dis. 2015; Oct 19. [5] Hagen M et al, J Rheum. 2018 Acknowledgement: Following further colleagues participated in the RETRO trial: C.Figueiredo, J.Cobra, HP.Tony, S.Finzel, S.Kleinert, J.Wendler, F.Schuch, M.Ronneberger, M.Feuchtenberger, M.Fleck, K.Manger, W.Ochs, M.Schmitt-Haendle, HM.Lorenz, H.Nüsslein, R. Alten, J.Henes, K.Krüger Disclosure of Interests: Melanie Hagen: None declared, Koray Tascilar: None declared, Michaela Reiser: None declared, Larissa Valor: None declared, Judith Haschka: None declared, Arnd Kleyer Grant/research support from: Lilly, Consultant for: Lilly, Speakers bureau: Abbvie, Axel Hueber: None declared, Bernhard Manger: None declared, Georg Schett: None declared, Jürgen Rech Grant/research support from: Bristol-Myers Squibb and Celgene (greater than 10, 000), Consultant for: Bristol-Myers Squibb, Celgene, Chugai, GlaxoSmithKline, Janssen, Eli Lilly, Novartis, Roche, Sanofi Aventis, and UCB (in total more than 10, 000), Speakers bureau: Bristol-Myers Squibb, Celgene, Chugai, GlaxoSmithKline, Janssen, Eli Lilly, Novartis, Roche, Sanofi Aventis, and UCB (in total more than 10, 000)